Structural Bridge Engineering - Mohd Haziman Wan Ibrahim; Norwati Jamaluddin; Noorwirdawati Ali; Shahrul Niza Mokhatar; Zainorizuan Mohd Jaini; Shahiron Shahidan (IntechOpen, 2016)
There are many books on preliminary studies and research in bridge design as well as basic knowledge on bridge engineering, but most books supply the needs of practicing engineers who may have problems in estimating, designing or constructing suspension bridges. Therefore, this book is intended to serve as a source of information for problems related to bridge engineering including sustainable bridge development, traditional approaches and recent advances in highway bridge traffic loading, aesthetic analysis issues in designing a new bridge, applications of various methods for the dissipation of seismic energy for bridges, new technologies of bridge design as well as structural identification of bridges using non-destructive experimental measurement tests.
English
Keywords: Engineering; Physical Sciences; Engineering and Technology; Structural Engineering; Civil Engineering